Fluid Inclusion and H–O–S–Pb Isotope Geochemistry of the Yuka Orogenic Gold Deposit, Northern Qaidam, China. (7th October 2019) - Cai, Pengjie; Xu, Rongke; Zheng, Youye; Yin, Yueming; Chen, Xin; Fan, Xianbin; Ma, Chao
Abstract : The Yuka gold deposit, located in the western part of northern Qaidam, contains Au orebodies hosted in early Paleozoic metamorphic basic volcaniclastic rocks. The Yuka mineralization can be divided into three stages: early quartz-pyrite (stage-I), middle quartz-gold-polymetallic sulfide (stage-II), and late quartz-carbonate (stage-III). Gold deposition is primarily contained within stage-II. Three types of fluid inclusions were identified in the vein mineral assemblages using petrography and laser Raman spectroscopy: H2 O-CO2 -NaCl (C-type), H2 O-NaCl (W-type), and pure CO2 (PC-type). Stage-I fluids record medium temperatures (205.2°C to 285.5°C) and H2 O-CO2 -NaCl±CH4 fluids with variable salinities (0.6–8.5 wt.% NaCl equiv.). Stage-II fluids evolved towards a more H2 O-rich composition within a H2 O-CO2 -NaCl±CH4 hydrothermal system at medium temperatures (193.1°C to 271.1°C), with variable salinities (0.4–11.7 wt.% NaCl equiv.). Stage-III fluids are almost pure H2 O and characterized by low temperatures (188.1°C to 248.5°C) and salinities (0.4–16.1 wt.% NaCl equiv.). These data indicate that ore-forming fluids are characterized by low to medium homogenization temperatures and low salinity and are evolved from a CO2 -rich metamorphogenic fluid to a CO2 -poor fluid due to inputs of meteoric waters, which is similar to orogenic-type gold deposits. The averageδ 18 O W of quartz varies from 3.3‰ in stage-I to 2.1‰ in stage-II and to 1.4‰ in stage-III, with theδ D values ranging from −41.6‰ to −58.5‰, suggesting that ore-forming fluids formed from metamorphic fluids mixed with meteoric waters. Auriferous pyriteδ 34 S ranges from 0.5 to 7.4‰ with a mean value of 4.43‰, suggesting that fluids were partially derived from Paleozoic rocks via fluid-wall rock interactions. Auriferous pyrites have 206 Pb/ 204 Pb of 18.238–18.600 (average of 18.313), 207 Pb/ 204 Pb of 15.590–15.618 (average of 15.604), and 208 Pb/ 204 Pb of 38.039–38.775 (average of 38.1697) and stem from the upper crust. Basing on geological characteristics of the ore deposit as well as new data from the ore-forming fluids, and H-O-S-Pb isotopes, the Yuka gold deposit is best described as an orogenic-type gold deposit.